Functional outcome of intramedullary nailing of the femoral shaft fracture - Sah, Sunil Kumar; Gyawali, Madan; Kandel, Prakriti Raj (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: A common fracture is a femoral shaft fracture. The advantages of intramedullary interlocking nails make them the method of choice for treating femoral shaft fractures. These benefits include a small incision, minimal dissection, decreased rates of infection, nonunion, and malunion, shorter hospital stays and rehabilitation periods, excellent union, rotational stability and length maintenance, rapid recovery, and early weight-bearing. Therefore, the aim of this study was to analyze the functional findings from femoral shaft fracture intramedullary nailing. Material and Methods: This was a hospital- based, longitudinal, observational study. All patients with femoral shaft fractures admitted at UCMS-TH, Bhairahawa from the Emergency Department managed surgically from October 2019 to March 2020 were included in the study. Femoral shaft fractures with age ≥ 16 years were included while open fractures (Gustalio and Anderson type 2 and 3), pathological fractures,congenital anomaly of the affected limb, previous fracture of the affected limb were excluded. All the patients were managed surgically and followed for at least 6 months. The outcome was measured by the Thoresen scoring system at the end of 6 months. Results: In this study of 30 cases, the mean age was 30.47 years, male and female ratio of 2:1, the left side was affected in 18 cases, RTA was the most common mode of injury. Most of the cases were Winquist and Hansen type 2 and AO type 32B. In the majority of the cases, 27 cases (90%) had no complication while superficial infection in 2 cases and shortening was seen in 1 case. We found excellent results in 86.7% cases, good in 10% cases and fair in 3.3% cases. Conclusion: The excellent functional outcome in terms of alignment and range of motion obtained in this study in the majority of patients makes this technique more reliable. The method of choice for femoral shaft fracture in adults was due to its low complication rate, high incidence of union, shorter hospital stay and early mobility.